The "Decennial Plan of Education": A project to improve Puerto Rico education system - Juan Lucas Onieva López (Universidad Nacional de Educación a Distancia (UNED), 2015)
The current educational system in Puerto Rico is trying to rise from a deep educational crisis. It has an index of abandon of around 40%, and every nine up to ten schools are under development plans, due to their students haven't achieved the goals established by the federal law No Child Left Behind. The politicization and privatization of the education among last years have demoralized both teachers and students, who in addition suffered a lack of the infrastructures and tools needed to teach and learn. To alleviate this situation the current Decennial Plan of Education has been developed since a few years until now. A project agreed by the educative community, parents and students, and which expects, from this year 2014, to carry on main changes into the educational system, such as the implantation of the Montessori model in Primary School or the depoliticization of the education.